PATHOGENETIC MECHANISMS OF CONVULSIVE DEPRESSIVE SYNDROME IN THE CONDITIONS OF KINDLING-INDUCED MODEL OF EPILEPTOGENESIS - Vastyanov, R.S.; Stoyanov, O.M.; Platonova, O.M.; Yermuraki, P.P.; Ostapenko, I.O.; Tatarko, S.V.; Bibikova, V.O. (World of Medicine and Biology, 2020)
Non-convulsive behavioral disorders are registered in the majority (over 75 %) of patients with epilepsy and are most often the only and most prominent manifestation of this disease. However, the neuropathogenetic mechanisms of these behavioral disorders remain insufficiently studied in the dynamics of chronic epileptogenesis, and the question of pathogenetically determined correction of non-convulsive epileptiform behavioral disorders is not considered in terms of comprehensive treatment of the chronic convulsive syndrome. The purpose of our work was to study the dynamics of the postural behavior severity in rats under the conditions of different periods of formation of picrotoxin-induced kindling using the striatal functional activity modulation. The obtained data indicate the hyperactivation of the striatum under the conditions of the development of picrotoxin-induced chronic convulsive activity, which functional activity depends on the term of the convulsive syndrome manifestation. The study of non-convulsive types of motor, emotional, swimming, cognitive behavior and their disorders during the specified time intervals of the formation of chronic epileptic activity is important for the use of certain behavioral disorders as an early diagnosis of epilepsy when the motor seizure disorders are absent and the probable behavior disorders do not reach maximum intensity
Keywords: kindling; postkindling; picrotoxin; non-convulsive behavioral disorders; postural behaviour; striatum; striatal neurotransmitter systems